2022
DOI: 10.1108/jeas-08-2021-0142
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of brand credibility and brand loyalty: the mediating effects of attitude toward brand

Abstract: PurposeCurrent research addresses the issue of brand loyalty while identifying its potential predictors. The research also examines the direct impact of brand credibility on brand loyalty and attitude toward brand and the direct impact of attitude toward brand and on brand loyalty respectively. Moreover, this research examines the mediating effect of attitude toward brand for the relationship of brand credibility and brand loyalty.Design/methodology/approachThis is a cross-sectional research. Data is collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 47 publications
1
11
0
9
Order By: Relevance
“…Some other variables that may influence consumer PI such as attitude toward the brand ( Choi and Rifon, 2012 ; Haq et al, 2022 ), perceived influencer trustworthiness ( Hsu et al, 2013 ; Magno and Cassia, 2018 ), level of involvement or influencer reputation ( Hsu et al, 2013 ) should be investigated further in future research ( Kapitan and Silvera, 2016 ). Future research could look into predictors of consumers’ perceptions of influence, like the lower-influencer emotional attachment ( Moussa and Touzani, 2017 ), perceived quality ( Wang and Lin, 2011 ), or online flow aspects ( Lim, 2014 ).…”
Section: Limitation and Future Directionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some other variables that may influence consumer PI such as attitude toward the brand ( Choi and Rifon, 2012 ; Haq et al, 2022 ), perceived influencer trustworthiness ( Hsu et al, 2013 ; Magno and Cassia, 2018 ), level of involvement or influencer reputation ( Hsu et al, 2013 ) should be investigated further in future research ( Kapitan and Silvera, 2016 ). Future research could look into predictors of consumers’ perceptions of influence, like the lower-influencer emotional attachment ( Moussa and Touzani, 2017 ), perceived quality ( Wang and Lin, 2011 ), or online flow aspects ( Lim, 2014 ).…”
Section: Limitation and Future Directionmentioning
confidence: 99%
“…Customers are being bombarded with more information on the internet every day, which has substantially lowered their attention span ( Veer et al, 2019 ). Many organizations have suffered financial difficulties in the market ( Kolte et al, 2018 ; Haq et al, 2022 ). The typical customer evaluation cycle’s period has been dramatically lowered and turned into a new shape.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, previous research has shown that customer experience with a brand can affect brand credibility (Dwivedi et al, 2018;Nayeem et al, 2019). Other research shows that brand credibility and trust positively affect brand loyalty (Akoglu, 2021;Haq et al, 2022;Song et al, 2019). Therefore, this research intends to examine the relationship between customer experience on brand loyalty mediated by brand credibility and brand trust, particularly in conventional travel agent services.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, brand loyalty can be affected by brand credibility and brand trust (Akoglu, 2021;Haq et al, 2022;Song et al, 2019). Brand credibility provides more advantages to customers and facilitates organizations to generate brand loyalty (Haq et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation